Short-term effect after soft tissue manipulation session on subjective and objective parameters in office workers with chronic low back pain: A randomized clinical trial - Michał Wendt; Jakub Rubach; Małgorzata Waszak (PLoS ONE, 2025)
Background The very frequent occurrence of low back pain (LBP) among office workers forces the search for effective therapeutic tools. The aim of this study was to assess the effectiveness of soft tissue manipulation (Deep Tissue Massage – DTM) on subjective and objective parameters in a group of office workers with chronic low back pain (CLBP). Materials and methods Forty participants aged 30–60 years with CLBP were randomly assigned to an experimental group (DTM, N = 20) or a control group (no therapy, N = 20). The intervention included four DTM sessions (45 minutes each over 2 weeks). Outcomes measured were lumbar range of motion (goniometer), pressure pain threshold of the longissimus muscle (algometer), and pain intensity (VAS). Assessments were performed one day prior to and one day following the therapy. Results DTM significantly improved lumbar spine mobility in the experimental group across all movement planes (Cohen’s d = 1.31–1.90), with significant between-group differences only for lumbar posterior flexion (p = 0.0149). A significant time effect was also observed for PPT, with an increase in the right-side threshold (p = 0.0186; d = 0.58). Pain intensity decreased significantly in the experimental group for maximum pain during the last week and during sitting (>30 min) (p ≤ 0.01; r = 0.79–0.90). No significant changes were observed in the control group, although a trend toward lower pain levels was noted in the experimental group after intervention. Conclusions Four DTM treatments resulted in reduced pain and increased spinal mobility in office workers suffering from chronic low back pain. However, further studies with a larger number of participants and an assessment of long-term effects are necessary. Clinical Trial Registration ClinicalTrials.gov NCT05690178